A report of the frequency of colorectal carcinoma and involved lymph nodes in South-West Iran - Shahbazian, Hodjatollah; Nasuri, Yaser; Hosseini, Seyed; Arvandi, Shoaleh; Razzaghi, Samira (Indian Journal of Medical and Paediatric Oncology, 2016)
Context: The colorectal cancer (CRC) is the most common malignancy between men and women. CRC has considerable morbidity and mortality, with more than 1000,000 new cases and 500,000 annual deaths. Regional lymph nodes are most common sites of metastasis from colon cancer. Lymph node involvement is an essential factor in enabling the accurate evaluation of prognosis in CRC patients. Aims: In this study, we focused on the frequency of CRC and involved lymph nodes and adequacy of lymph node dissection in patients who referred to the Oncology and Radiotherapy Department of Golestan Hospital in Ahvaz City located in South-West Iran. Setting and Design: We conducted a retrospective study among patients receiving surgical treatment for CRC in the Department of Oncology and Radiotherapy of Golestan Hospital in Ahvaz City located in South-West Iran between 2001 and 2010. Methods and Materials: All patients who underwent resection for CRC by open or laparoscopic approaches were included in the study. Data were collected from patients′ medical records. Statistical Analysis Used: Statistical data were analyzed using SPSS 21. Results: A total of 585 cases with CRC aged from16 to 89 years with mean age of 53-year-old were studied. Average number of dissected nodes was 8 lymph nodes, and lymph nodes were not found in pathology specimen of 61 cases (10.4%). In 199 patients (34.01%), number of dissected lymph nodes was 12 or more and in 386 patients (65.98%), number of dissected lymph nodes was <12. Conclusion: This study revealed a large amount of patients that had been under over treatment with radiotherapy and the following inability. Lack of removal of sufficient tissue by the surgeon during surgery or an inadequate sample check by a pathologist might lead to an inability to correct staging of the disease as well as the inability to determine the treatment program of the patients and over treatment with radiotherapy and chemotherapy.
Keywords: Colorectal cancer; lymph node dissection; lymph node metastasis